(untitled) (Journal of Organizational Psychology, 2023)
Manuscript investigates the use of human resource management (HRM) practices to address traumatic stress and compassion fatigue among certified nurse aides (CNAs) working in institutional long term care (ILTC) facilities. Instituting HRM practices to address traumatic stress and compassion fatigue among CNAs are one way ILTC facilities can proactively confront the consequences of traumatic stress and compassion fatigue. CNAs provide much of the resident care in ILTC facilities and the effects of traumatic stress and compassion fatigue on CNAs are very important for both ILTC facilities and their residents. Specific HRM practices in the areas of staffing, training and development, and compensation management useful in addressing traumatic stress and compassion fatigue among CNAs are presented and discussed.